1983
DOI: 10.1111/j.2042-3306.1983.tb01813.x
|View full text |Cite
|
Sign up to set email alerts
|

Follicle stimulating hormone, luteinising hormone and progesterone concentrations in the blood of Thoroughbred mares exhibiting single and twin ovulations

Abstract: Summary The concentrations of follicle stimulating hormone, luteinising hormone and progesterone were measured in serial blood samples taken throughout one or more oestrous cycles from 12 Thoroughbred mares, some of which exhibited single and others twin ovulations. The resulting profiles clearly demonstrated that no simple relationship exists between circulating gonadotrophin levels and subsequent ovulation rate in the mare. However, plasma progesterone concentrations during dioestrus are, as expected, higher… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
6
1
1

Year Published

1985
1985
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 14 publications
0
6
1
1
Order By: Relevance
“…The lower LH likely reflected, at least in part, the greater concentrations of progesterone on the corresponding days. Previous reports have documented higher concentrations of progesterone during dioestrus in mares that had multiple ovulations (Henry et al 1982;Urwin and Allen 1983;Squires et al 1987) but did not indicate that the higher progesterone in doubleovulating mares begins immediately after the ovulations. Support for the interpretation that the lower postovulation LH in the group with multiple ovulations results from higher progesterone is the demonstration of a negative effect of exogenous progesterone on LH (Gastal et al 1999a(Gastal et al , 2000.…”
Section: Discussionmentioning
confidence: 89%
See 1 more Smart Citation
“…The lower LH likely reflected, at least in part, the greater concentrations of progesterone on the corresponding days. Previous reports have documented higher concentrations of progesterone during dioestrus in mares that had multiple ovulations (Henry et al 1982;Urwin and Allen 1983;Squires et al 1987) but did not indicate that the higher progesterone in doubleovulating mares begins immediately after the ovulations. Support for the interpretation that the lower postovulation LH in the group with multiple ovulations results from higher progesterone is the demonstration of a negative effect of exogenous progesterone on LH (Gastal et al 1999a(Gastal et al , 2000.…”
Section: Discussionmentioning
confidence: 89%
“…Previous reports have documented higher concentrations of progesterone during dioestrus in mares that had multiple ovulations (Henry et al. 1982; Urwin and Allen 1983; Squires et al. 1987) but did not indicate that the higher progesterone in double‐ovulating mares begins immediately after the ovulations.…”
Section: Discussionmentioning
confidence: 90%
“…Furthermore, heritability is also unlikely as a full sister and a half sister to the mare in question both showed normal ovulatory patterns. Circulating FSH and LH concentrations in double ovulating mares have not been found to differ from those in mares with single ovulations (Urwin and Allen 1983;Squires et al 1987). However, in a case like the present mare, which showed extreme deviations from the normal, physiological ovulation rate, hormonal aberrations, either at the production or receptor levels, is very likely to underlie the phenomenon.…”
Section: Discussionmentioning
confidence: 98%
“…In the mare, circulating progesterone concentrations have been reported to be higher after double ovulations than after a single ovulation (Palmer and Jousset 1975;Henry et al 1982;Urwin and Allen 1983;Squires et al 1987). In the present case, plasma progesterone concentration reached only 14 ng/ml during the first week of pregnancy and was therefore no higher than the levels reported in previous studies (Squires eta/.…”
Section: Discussionmentioning
confidence: 99%
“…The higher plasma progesterone concentration in mares with twins in comparison to mares carrying singletons is consistent with findings from other studies. Urwin and Allen demonstrated that higher levels of progesterone were observed in mares with double ovulations. Ginther showed that progesterone was significantly higher in mares with multiple ovulations compared with single ovulations beginning Day 1 post ovulation to Day 4 post ovulation.…”
Section: Discussionmentioning
confidence: 98%